2015
DOI: 10.3389/fmicb.2015.00981
|View full text |Cite
|
Sign up to set email alerts
|

Application of tea polyphenols in combination with 6-gingerol on shrimp paste of during storage: biogenic amines formation and quality determination

Abstract: Tea polyphenols (TP) have shown antioxidant activity and antimicrobial properties in the food industry. Assessment of anti-oxidation potential of 6-gingerol (GR) has also been verified. As little is known about the use of tea polyphenols either individually or in combination with 6-gingerol in shrimp paste, we aimed to investigate the effect of tea polyphenols combined with 6-gingerol on the biogenic amines inhibition and quality of shrimp paste stored at 25°C for 160 days. The shrimp paste samples were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…There was no significant difference between control and PO groups in TPC ( P > 0.05) during refrigerated storage, while TPC of GI and PO + GI groups was significantly lower than that of the other two groups after day 9 ( P < 0.05). The antimicrobial activity of ginger and ginger extract was widely investigated, which has been applied to shrimp paste, red sea bream, smoked mackerel and red drum fish fillets to inhibit microbial growth and improve aquatic product quality . Similar results were observed in this study because 6‐gingerol could perform well in inhibiting TPC increase of grass carp surimi during refrigerated storage.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…There was no significant difference between control and PO groups in TPC ( P > 0.05) during refrigerated storage, while TPC of GI and PO + GI groups was significantly lower than that of the other two groups after day 9 ( P < 0.05). The antimicrobial activity of ginger and ginger extract was widely investigated, which has been applied to shrimp paste, red sea bream, smoked mackerel and red drum fish fillets to inhibit microbial growth and improve aquatic product quality . Similar results were observed in this study because 6‐gingerol could perform well in inhibiting TPC increase of grass carp surimi during refrigerated storage.…”
Section: Resultssupporting
confidence: 83%
“…It has been proposed that 6‐gingerol could scavenge free radicals through hydrogen atom and sequential electron proton transferring mechanisms that prevented the propagation chain reaction during lipid oxidation . These results were also confirmed by Cai et al ., who observed that shrimp paste treated with 6‐gingerol inhibited the increase in TBARS during storage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TMA-N reached 13.9 mg/100 g in the controls, and 11.93 and 11.86 mg/100 g in the HM-and AM-treated shrimp, respectively. Stronger prevention of TMA-N increase was reported during cold storage of megrim [28] treated with and without F. spiralis, where the final TMA-N ranged from 193.3-240.7 mg/100 g for the controls, and 0.67-2.50 g for the shrimp treated with F. spiralis. However, in the present study, TMA-N mainly indicated that the red seaweed solutions, particularly HM, effectively inhibited the decarboxylation of trimethylamine oxide to trimethylamine.…”
Section: Resultsmentioning
confidence: 85%